Pembentukan Karakter Peduli Sosial Melalui Pembelajaran IPS di SDI Ende 14 - Raji, Manggu Ngguna; Korosando, Fransiskus (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research aims to describe the formation of social caring character through learning Social Sciences at SDI Ende 14, Mautapaga Village, East Ende District, Ende Flores Regency, East Nusa Tenggara. This study uses a qualitative method. Data collection techniques in this research were interviews, observation and documentation as well as questionnaires. The data analysis techniques in this research are data reduction, data presentation and drawing conclusions. The results of this research show that the formation of a socially caring character through learning Social Sciences is able to change the character of students for the better. Apart from learning in class, social care character formation is carried out through direct learning practices. After getting the theory from the teacher and being able to practice it in direct learning, students apply the character of social care, it becomes a habit and becomes a culture at SDI Ende 14, Mautapaga Village, East Ende District, Ende Flores Regency, East Nusa Tenggara.